Distribution and conservation status of the American Crocodile (Crocodylidae: Crocodylus acutus) in El Salvador (UNED Research Journal, 2022)
Introduction: The American Crocodile (Crocodylus acutus) is a top predator and can be considered a keystone species is its ecosystems. Even though the species has often been studied elsewhere, there is little information about its current distribution and status in El Salvador. Objective: To update the geographic distribution, and to assess its conservation status, in El Salvador. Methods: We defined a potential distribution model for nine climatic factors with DOMAIN, a bioclimatic modeling program. Location was compiled from the literature; observations and photographs by biologists and rangers; and state records. We defined status with International Union for Conservation of Nature guidelines. Results: The crocodile was reported from 40 localities, including all departments of the coastal zone and in artificial reservoirs in the center of the country. There is a close relationship between the records and the hydrological systems of the Lempa, Grande San Miguel and Goascorán rivers. The sites with the highest numbers of records are Bahía de La Unión, the mouth of the Lempa River and Barra de Santiago. The potential distribution covers 29% of the country, with only 8 % in protected areas. The species is considered extirpated from Lake Güija. Many specimens are translocated to avoid accidents with humans. Conclusion: The crocodile is widely distributed in El Salvador river systems, but management is still needed and should be improved, covering research, education, and protection.
Keywords: enviromental conflicts; endangered species; distribution; wetlands; mangroves